A desconsideração da personalidade jurídica na aplicação das penas restritivas do direito de licitar e contratar - Pires, Antonio Cecílio Moreira (2012)
The scope of this study was to examine the possibility of disregarding the legal entities in the application of the penalties restricting the right to bid and contract with the Public Administration, brought for the Laws 8.666/93 and 10.520/02. The choice of subject is justified on the grounds that the shareholders of the companies bidding participants, when sanctioned by any of the penalties restricting the right to bid and hire with the Public Administration, are in another company, often with the same partners, social object and address .The reason they continue to bid and contract with the government, in a clear breach and abuse of the law, which is supported by the Public Administration due to the lack of formal law to authorize the disregard of the legal entity of these companies. The present work involved research and examination of doctrine, national and foreigner, as well as legislation and concrete cases in the jurisprudence. We start with the concept of the norm and the illegal, through the examination of administrative penalty and its legal system to, soon after, analyze the penalties provided for the art. 87, III and IV, of Law 8.666/93 and art. 7, of Law 10.520/02, highlighting the "sine qua non" condition of the instauration of the administrative process, as required for the Law 9.784/99, in obedience to the principle of due process, until we get to the disregard of the legal entity in the context of the general theory of law. Finally, we examine the disregard of the legal entity in the application of penalties restricting the right to bid and hire with the Public Administration, sustaining the principle of morality, unavailability of public interest, efficiency and impartiality, and the mandatory principles of motivation, reasonableness and proportionality, as a way to attend to the substantive due process